Range-wide monitoring reveals demographic vulnerability in Lahille's bottlenose dolphins - Fábio G. Daura-Jorge; Paula Laporta; Ignacio B. Moreno; Paulo H. Ott; Paulo A.C. Flores; Pedro Volkmer de Castilho; André S. Barreto; Rodrigo Cezar Genoves; Carolina Bezamat; Alexandre M.S. Machado; Eduardo R. Secchi; Silvina Botta; et al. (Biological Conservation, 2026)

Leiomyoma Causing Disease in a Wild Adriatic Sturgeon ( Acipenser naccarii , Bonaparte, 1836) - A. Marsella; T. Pretto; C. Samassa; P. Tedesco; F. Pascoli; L. Congiu; A. Gustinelli; F. Borghesan; A. Toffan (Journal of Fish Diseases, 2025)
The Adriatic sturgeon, Acipenser naccarii , is an endemic species to the Adriatic Sea basin classified as critically endangered according to the IUCN Red List. Limited information is available regarding the health status and diseases affecting this species, particularly in the wild. In September 2023, a post‐spawning female Adriatic sturgeon was found along the edges of the Adige River. The fish displayed abnormal swimming, cutaneous haemorrhages, extreme emaciation and died shortly after its finding. At necropsy, the stomach appeared enlarged with a firm texture and a severe restriction of the lumen due to the thickening of the gastric wall. A gastric leiomyoma was characterised by histology, and this represents the first description of such neoplasia in A. naccarii . In the intestine, a severe infestation with roundworm belonging to the phylum Acanthocephala was responsible for severe haemorrhagic enteritis. The parasites were identified as belonging to the species Leptorhynchoides polycristatus , providing the first description of such a parasite in Italy. Finally, genetic analyses were performed in order to assess genetic purity and relatedness with captive breeding stocks. The results showed that the individual did not cluster with any captive identified groups, supporting the likelihood of a pure and wild‐origin Adriatic sturgeon.

Mandibular anatomy of a new specimen of a prozostrodontian cynodont (Eucynodontia: Probainognathia) from the Upper Triassic of Brazil - Pedro Henrique Dotto; Lívia Roese-Miron; Sérgio F. Cabreira; Lúcio Roberto-da-Silva; Flavio A. Pretto; Leonardo Kerber (The Science of Nature, 2025)

Plant invasions on small Mediterranean islands: An overview - L. Celesti-Grapow; L. Bassi; G. Brundu; I. Camarda; E. Carli; G. D’Auria; E. Del Guacchio; G. Domina; G. Ferretti; B. Foggi; L. Lazzaro; P. Mazzola; et al. (Plant Biosystems, 2016)

Betanodavirus ability to infect juvenile European sea bass, Dicentrarchus labrax , at different water salinity - F Pascoli; M Serra; M Toson; T Pretto; A Toffan (Journal of Fish Diseases, 2016)
Viral encephalopathy and retinopathy ( VER ) is one of the most devastating and economically relevant diseases for marine aquaculture. The presence of betanodavirus in freshwater fish is recorded, but very little is known about VER outbreaks in marine species reared in freshwater. Our study investigated the ability of betanodavirus to cause disease in European sea bass, Dicentrarchus labrax, reared at different salinity levels. Fish were challenged with RGNNV or mock infected by bath at different salinity levels (freshwater, 25‰ and 33‰). Fish were checked twice a day and the dead ones were examined by standard virological techniques, by rRT ‐ PCR and by histochemical and immunohistochemical analyses. All the infected groups showed a significant higher mortality rate than the one of the mock‐infected group. VER v presence was confirmed by rRT ‐ PCR . Histochemical and immunohistochemical analyses highlighted the typical lesions associated with VER . Our results highlight that salinity does not affect the ability of betanodavirus to induce clinical signs and mortality in European sea bass infected under experimental conditions. These results underline the great adaptation potential of VER v, which in combination with its already known high environmental resistance and broad host range, may explain the diffusion of this disease and the threat posed to aquaculture worldwide.

Woody flora as a predictor of vascular plant richness: An insight in Italy - G. Abbate; S. Bonacquisti; S. Burrascano; E. Giovi; A. Giuliani; F. Pretto; E. Scassellati (Plant Biosystems, 2015)

Determinants of non-native plant species richness and composition across small Mediterranean islands - F. Pretto; L. Celesti-Grapow; E. Carli; G. Brundu; C. Blasi (Biological Invasions, 2012)

Viral encephalopathy and retinopathy outbreak in restocking facilities of the endangered freshwater species, S alaria fluviatilis (Asso) - N Vendramin; F Padrós; T Pretto; E Cappellozza; V Panzarin; G Bovo; A Toffan; C Terregino (Journal of Fish Diseases, 2012)

Influence of past land use and current human disturbance on non-native plant species on small Italian islands - F. Pretto; L. Celesti-Grapow; E. Carli; C. Blasi (Plant Ecology, 2010)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)